KEMAMPUAN GURU SEKOLAH DASAR MATOANGING 3 DALAM MENYUSUN SOAL TIPE Higher Order Thinking Skill - Jamaluddin, Jaja; Setiawan, Adil (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
One of the competencies that must be possessed by a teacher is pedagogic competence which consists of the ability of the teacher to manage learning outcomes. Teachers are required to be able to compile learning evaluation instruments with the aim of being able to learn from acceptable learning outcomes. The purpose of this study was to study the ability of elementary school teachers at SD Matoanging 3, namely in making questions about Higher Order Thinking Skills. This research method is analytic descriptive. The results showed that the ability of Matoanging State Elementary School 3 teachers to develop high-level thinking type skills was still very weak. Above 60% of the teacher's ability to develop high-order thinking skills questions is very weak, 30% is sufficiently capable and only 10% of teachers in Matoanging Public Elementary School 3 are able to arrange high-level thinking skills.